Implications of the Immune Landscape in COPD and Lung Cancer: Smoking Versus Other Causes - Taucher, Elisabeth; Mykoliuk, Iurii; Lindenmann, Joerg; Smolle-Juettner, Freyja-Maria (Frontiers in Immunology, 2022)
Cigarette smoking is reported in about one third of adults worldwide. A strong relationship between cigarette smoke exposure and chronic obstructive pulmonary disease (COPD) as well as lung cancer has been proven. However, about 15% of lung cancer cases, and between one fourth and one third of COPD cases, occur in never-smokers. The effects of cigarette smoke on the innate as well as the adaptive immune system have been widely investigated. It is assumed that certain immunologic features contribute to lung cancer and COPD development in the absence of smoking as the major risk factor. In this article, we review different immunological aspects of lung cancer and COPD with a special focus on non-smoking related risk factors.